2016
DOI: 10.18052/www.scipress.com/ilns.57.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salinity Stress on Growth and Phenolics of Rice (<i>Oryza sativa</i> L.)

Abstract: Abstract. This study was conducted to determine the correlation between of salinity stress on growth and phenolic compounds in rice. It was observed that salinity stress caused a significant decrease in shoot lengths, fresh and dry weights of all rice varieties. Under salinity stress, changes of chemical contents also differed among phenolic compounds and rice cultivars. Total phenolics and flavonoids, and contents of vanillin and protocatechuic acid in tolerant varieties were strongly increased, whereas in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 35 publications
6
21
0
1
Order By: Relevance
“…The damage from MG is diminished in plants through the action of the glyoxylase system, which consists of the glyoxalase I (Gly I) and glyoxalase II (Gly II) enzymes that detoxify MG [9].Both enzymatic and nonenzymatic antioxidants work simultaneously to combat the deleterious effects of oxidative stress caused by exposure to abiotic factors such as Cd. However, another notable response to several abiotic stresses is a marked accumulation of phenolic compounds [10][11][12][13][14]. Some phenolics have the capability to scavenge ROS directly as a way to reduce oxidative stress [11].…”
mentioning
confidence: 99%
“…The damage from MG is diminished in plants through the action of the glyoxylase system, which consists of the glyoxalase I (Gly I) and glyoxalase II (Gly II) enzymes that detoxify MG [9].Both enzymatic and nonenzymatic antioxidants work simultaneously to combat the deleterious effects of oxidative stress caused by exposure to abiotic factors such as Cd. However, another notable response to several abiotic stresses is a marked accumulation of phenolic compounds [10][11][12][13][14]. Some phenolics have the capability to scavenge ROS directly as a way to reduce oxidative stress [11].…”
mentioning
confidence: 99%
“…It was observed that salt-tolerant varieties exhibited greater total phenolic content, flavonoid content, and phenolic acid levels in comparison with salinity-susceptible varieties. The study also stated that ferulic and p-coumaric acids are potentially linked to the salinity resistance mechanism as these two compounds were only observed in salt-tolerant varieties (Minh et al, 2016). In addition, studies by Daiponmak et al (2010) and Umnajkitikorn et al (2013) also demonstrated that increase in salinity to a certain level increased antioxidant activity in rice.…”
Section: Salinity and Water Deficiencymentioning
confidence: 91%
“…The relationship between salt tolerance and phenolic content of rice was also examined by Minh et al. () on six rice varieties. It was observed that salt‐tolerant varieties exhibited greater total phenolic content, flavonoid content, and phenolic acid levels in comparison with salinity‐susceptible varieties.…”
Section: Environmental Effect On Cereal Phenolic Contentmentioning
confidence: 99%
See 2 more Smart Citations